The COVID‐19 pandemic: A rapid global response for children with cancer from SIOP, COG, SIOP‐E, SIOP‐PODC, IPSO, PROS, CCI, and St Jude Global. Issue 7 (13th May 2020) - Sullivan, Michael; Bouffet, Eric; Rodriguez‐Galindo, Carlos; Luna‐Fineman, Sandra; Khan, Muhammad Saghir; Kearns, Pam; Hawkins, Douglas S.; Challinor, Julia; Morrissey, Lisa; Fuchs, Jörg; Marcus, Karen; Balduzzi, Adriana; et al.
Abstract: The COVID‐19 pandemic is one of the most serious global challenges to delivering affordable and equitable treatment to children with cancer we have witnessed in the last few decades. This Special Report aims to summarize general principles for continuing multidisciplinary care during the SARS‐CoV‐2 (COVID‐19) pandemic. With contributions from the leadership of the International Society for Pediatric Oncology (SIOP), Children's Oncology Group (COG), St Jude Global program, and Childhood Cancer International, we have sought to provide a framework for healthcare teams caring for children with cancer during the pandemic. We anticipate the burden will fall particularly heavily on children, their families, and cancer services in low‐ and middle‐income countries. Therefore, we have brought together the relevant clinical leads from SIOP Europe, COG, and SIOP‐PODC (Pediatric Oncology in Developing Countries) to focus on the six most curable cancers that are part of the WHO Global Initiative in Childhood Cancer. We provide some practical advice for adapting diagnostic and treatment protocols for children with cancer during the pandemic, the measures taken to contain it (e.g., extreme social distancing), and how to prepare for the anticipated recovery period.